(untitled) (The Review of Diabetic Studies, 2024)
Background: Emergency anesthesia in patients with diabetes mellitus is associated with elevated risks of peri-anesthetic complications, particularly hypoglycemia, hyperglycemia, and medication-related adverse events. These risks are amplified in emergency settings due to time constraints, incomplete clinical information, and complex interprofessional workflows. While the roles of anesthesiologists, nurses, and pharmacists are well established, the contribution of medical secretariat professionals to anesthesia safety and health security remains insufficiently explored. Aim: This narrative review aims to examine the role of the medical secretariat in enhancing health security and emergency anesthesia safety for diabetic patients through structured coordination with nursing and pharmacy staff. Methods: A narrative review approach was employed, synthesizing evidence from peer-reviewed literature on emergency anesthesia safety, perioperative diabetes management, interprofessional collaboration, and patient safety systems. Relevant guidelines and conceptual frameworks related to health security and systems-based safety models were also reviewed. Results: The findings indicate that medical secretariats play a critical role at the administrative–clinical interface by supporting accurate documentation, facilitating timely information exchange, and coordinating medication-related processes. These functions contribute to reducing communication failures, preventing medication errors, and improving continuity of care during emergency anesthesia. Secretariat-mediated coordination was found to align with high-reliability organization principles and systems-based patient safety models, reinforcing multiple layers of defense against preventable harm. Conclusion: Medical secretariats represent a key yet under-recognized component of emergency anesthesia safety for patients with diabetes mellitus. Integrating their roles into emergency anesthesia workflows and health security frameworks may enhance system resilience, strengthen interprofessional collaboration, and improve patient safety outcomes. Further empirical research is warranted to evaluate the impact of structured medical secretariat integration on clinical and organizational performance indicators.